The macroeconomic loss due to violence against women and girls: The case of Ghana - Srinivas Raghavendra; Kijong Kim; Sinead Ashe; Mrinal Chadha; Felix Ankomah Asante; Petri T. Piiroinen; Nata Duvvury (Levy Economics Institute of Bard College, 2019)
Violence against women and girls (VAWG) is a widely recognized human rights violation with serious consequences for the health and well-being of women and their families. However, the wider ramifications of VAWG for businesses, communities, economies, and societies are only recently being recognized. Despite this recognition, there are few studies exploring how the economic and social impacts of VAWG affect economic growth, development, and social stability. In this paper, applying the social accounting approach, we outline the ripple effects of VAWG from the individual micro-level impacts to the macroeconomy. Our analysis shows the loss due to VAWG amounts to about 0.94 percent of Ghanaian GDP and is a permanent invisible leakage from the circular flow of the economy. The analysis also shows that the loss due to violence is not just a one-off leakage from the macroeconomic circular flow and explores the potential consequences of the multiplier loss due to VAWG over a period of time. The cumulative loss is sizeable and inflicts a premium on GDP growth over time-in simple terms, inaction today in addressing VAWG for cost considerations will impose a larger cost premium on economic growth, which will constrain tomorrow's resources.
Keywords: E16; E19; E71; J16; B54; O55; 330; Violence against Women and Girls; Social Accounting Matrix; Productivity Loss; Economic Growth